1998
DOI: 10.1149/1.1838898
|View full text |Cite
|
Sign up to set email alerts
|

Remote Plasma‐Enhanced Chemical Vapor Deposition of SiO2 Using Ar/  N 2 O  and SiH4

Abstract: Remote plasma-enhanced chemical vapor deposition of Si02 using a radio-frequency (rf) Ar/N20 plasma and downstream-injected SiH4 was investigated. The deposition rate at 20 W rf power was measured as a function of pressure, temperature, and SiH4 flow rate. The Si02 deposition rate at 300°C and 300 mTorr depends linearly on the SiH4 flow rate. The deposition rate is independent of N30 flow rate for N20/SiH4 ratios much greater than 1, consistent with oxygen saturation of the growth surface. The deposition rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…As a result, the concentrations of all gas phase species that are included in the heterogeneous chemistry mechanism are by several orders magnitude in the case of MTS before partial equilibrium is reached (see Figures 2 and 7). From the evolution of the rates of the elementary reactions in the homogeneous chemistry mechanism, it was concluded in the preceding section that the higher concentrations of Si in accordance with the results of the analysis of the gas phase of silicon oxide CVD reactors using spectroscopic methods [68,69].…”
Section: Overall Modelsupporting
confidence: 60%
“…As a result, the concentrations of all gas phase species that are included in the heterogeneous chemistry mechanism are by several orders magnitude in the case of MTS before partial equilibrium is reached (see Figures 2 and 7). From the evolution of the rates of the elementary reactions in the homogeneous chemistry mechanism, it was concluded in the preceding section that the higher concentrations of Si in accordance with the results of the analysis of the gas phase of silicon oxide CVD reactors using spectroscopic methods [68,69].…”
Section: Overall Modelsupporting
confidence: 60%
“…RF discharges in N 2 O + SiH 4 mixtures are used for depositing amorphous oxynitrides films (a-SiN x O y and a-SiN x O y : H) [3][4][5][6][7]. In a number of cases rf discharges in N 2 O + SiH 4 mixtures are used to deposit SiO 2 films [8][9][10][11][12]. Typically the N 2 O concentration in the N 2 O + SiH 4 mixture is 2-40 times higher than that of silane.…”
Section: Introductionmentioning
confidence: 99%
“…where current is in amperes and pressure is in Torr. Finally, using the ionization gauge sensitivity ratios of Nakao [14], the calibration equation for this fast ionization gauge in air is (5) III. TRANSIENT PRESSURE MODEL…”
Section: Methodsmentioning
confidence: 99%
“…Earlier investigations have shown that deposition rate is a strong function of monomer pressure [1]- [6]. For example, it has been observed in continuous plasma reactors that as pressure is increased deposition rates reach a maximum and then plateau or decrease [1], [5], [6]. This phenomenon was explained by assuming a change in deposition mechanism occurs above a certain pressure leading to an increased particle formation in the gas phase [5], [7].…”
Section: Modeling and Measurement Of Monomer Pressure Evolution In Anmentioning
confidence: 99%
See 1 more Smart Citation